Public Sentiment on Sustainable Finance and Implications for Islamic Banks - Septiana, Nurul Izzati; Swandaru, Randi; Hudaefi, Fahmi Ali (Jurnal REKSA: Rekayasa Keuangan, Syariah dan Audit, 2024)
This paper attempts to identify the challenges and strategies for implementing sustainable finance in Islamic banking and to analyze public opinion on sustainable finance on the Twitter platform using sentiment analysis. The research methods used in this study are the Analytical Network Process (ANP) method to answer the first research objective and the sentiment analysis method, which can assess public opinion based on emotions and sentiments in a particular text to answer the second research objective. The results of the study identified several challenges and priority strategies for implementing sustainable finance in Islamic banks. They identified the sentiment of words that can be used to design communication strategies to create a positive image for the company because it is associated with sustainable finance. This study may contribute to enhancing the implementation of sustainable finance in Islamic banks and better communicating with the public on this matter.